MANAGING â€œENGLISH FOR NURSINGâ€ (EFN) COURSE IN HIGHER EDUCATION WITH CONSTRUCTIVISM - Naeli Rosyidah (Universitas Sarjanawiyata Tamansiswa, 2021)
The English skills for the nursing students in Indonesian Higher Education need to be prepared to be able to increase the English communication skills and to avoid miscommunication and malpractice. English in Indonesia is regarded as Foreign Language, so it is not surprising if many nurses still have low English skills. Managing â€œEnglish for Nursingâ€ (EfN) course in higher education should be constructed with effective approaches one of which is constructivism. Constructivism in EfN is better conducted with some techniques including the use of technology, flash cards /situation cards, real medical tools, and forms. Hence, the students will understand the contextual situation and can construct the appropriate expressions. The implementation of the constructivist uses in EfN classes must be adjusted with the studentsâ€™ level to achieve the purpose.